THE PRACTICE OF ISLAMIC ECONOMICS, SOCIAL INSTITUTIONS, AND VILLAGE SOCIAL NETWORKS IN EFFORTS TO IMPROVE THE ECONOMY OF THE MENGKALAN JAMBU VILLAGE COMMUNITY - Agustar, Agustar; Setiadi, Iwan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study seeks to examine the influence of Islamic economic practices, village social institutions, and social networks on economic improvement in Mengkalang Jambu Village. The research adopts a qualitative descriptive approach, involving 11 informants. The findings reveal the following: 1) The residents of Mengkalang Jambu Village engage in Islamic economic practices in their economic activities; however, these practices have not significantly contributed to economic improvement in the community. 2) Social institutions exist within the village, yet their roles have been insufficient in promoting economic growth for the residents. 3) The village community includes two main social networks, specifically the traditional community group and a local copra farmer group. Despite their presence, these social networks have not substantially enhanced economic conditions for the people of Mengkalang Jambu Village.